The emergence of modern intellectual Currents: The Aqeeqah feast between the permissible and the forbidden in northern Togo “Cinkasse” - Youssif, Ibrahim (Arab Journal for Sciences and Research Publishing, 2024)
Just as the Aqeeqah feast is one of the controversial issues among scholars, it should not be a cause for disputes and excommunication of one another, as happens in northern Togo (Cinkasse) by dividing one group into two groups, or creating a new sect. Yes, a dispute may occur between a group on a religious issue. But it does not go beyond division, because Islamic law calls and urges unity and meeting, and rejects division and dispersion. Therefore, this research will address the Aqeeqah and its feast, meaning the definition of the Aqeeqah and its feast and the ruling on the Aqeeqah and its feast, knowing that the Aqeeqah is one of the rituals of the religion of Islam, so the rulings on the Aqeeqah and its matter should be detailed. Her feast is clear and clear, especially since the Aqeeqah feast is the reason for the separation or creation of a new group in Cinkasse. I will collect the statements of some scholars and their evidence on this jurisprudential issue, and I will simplify the matter of the Aqeeqah feast and that it is not permissible to dispute, let alone declaring each other to be infidels, as happened in Cinkasse. Therefore, the Muslim community should be aware that the issue of the Aqeeqah is fundamentally a different matter, let alone the Aqeeqah, and that it is not one of the pillars of Islam, and one should be careful not to declare people infidels for the sake of the Aqeeqah feast.
Keywords: Contemporary intellectual currents; the Aqeeqah feast; permissibl; forbidden; Cinkasse